Association of Epidermal Growth Factor Receptor Mutations with Metastatic Presentations in Non-Small Cell Lung Cancer. (31st March 2011) - Na, Im Il; Park, Jong Heon; Choe, Du Hwan; Lee, Jin Kyung; Koh, Jae Soo
Abstract : We performed this retrospective study to assess the association of epidermal growth factor receptor (EGFR) with metastatic presentations in advanced non-small cell lung cancer (NSCLC). The data from 125 patients with stage III or IV NSCLC were analyzed. We detected EGFR mutations in 36 NSCLC patients. EGFR mutations were predominant in never-smokers( P < .001 ), patients with adenocarcinomas( P < .001 ), and female patients( P < .001 ) . When the metastatic sites were analyzed, pleural metastases were associated with a high incidence of EGFR mutations( P = .028 ) . Particularly, pleural metastases with minimal effusion (PMME) were associated with EGFR mutational status( P = .001 ) . Patients with N3 lesions were less likely to harbor EGFR mutations( P = .033 ) . On multivariate analysis, N3 lesions( P = .017 ) and PMME( P < .001 ) remained significant factors for EGFR mutations. EGFR mutations may be associated with different presentations of pleural and N3 nodal metastases.